The spectacle self: Indonesian youth’s self-presentation through Instagram “flexing culture” - Mashita Phitaloka Fandia Purwaningtyas; Viridian Mangsah Puspandara (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2026)
“Flexing culture” on Instagram is one of consequences of social media’s embeddedness in the lives of young people, particularly in Indonesia. To date, research on “flexing culture” tends to discuss it from a psychological or economic perspective, meanwhile there were limited studies that regarded “flexing culture” as cultural production/reproduction of meaning and how the culture might shape the self/identity of young users. This paper aims to analyze the practice of “flexing culture” on Instagram from the lens of Indonesian youth, by conducting virtual ethnography research as method. In this study, it is found that youth tend to define “flexing” as a spectrum between the efforts of personal branding and the practice of oversharing. This meaning then constructs the youth’s self-presentation that is manifested in the practice of “flexing” in forms of “spectacle self”; which refers to the mediated representation of self-image which is based on flexing contents.